2019
DOI: 10.3390/s19204448
|View full text |Cite
|
Sign up to set email alerts
|

Wearables and the Quantified Self: Systematic Benchmarking of Physiological Sensors

Abstract: Wearable sensors are increasingly used in research, as well as for personal and private purposes. A variety of scientific studies are based on physiological measurements from such rather low-cost wearables. That said, how accurate are such measurements compared to measurements from well-calibrated, high-quality laboratory equipment used in psychological and medical research? The answer to this question, undoubtedly impacts the reliability of a study’s results. In this paper, we demonstrate an approach to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…As such, this allows for apples-to-apples comparison. In addition, Schmidt et al’s work is comprehensive in terms of the machine learning algorithms examined, and their results are comparable to what has been reported recently on using machine learning approaches for stress detection [ 16 ].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…As such, this allows for apples-to-apples comparison. In addition, Schmidt et al’s work is comprehensive in terms of the machine learning algorithms examined, and their results are comparable to what has been reported recently on using machine learning approaches for stress detection [ 16 ].…”
Section: Resultssupporting
confidence: 68%
“…Much research has been conducted on using physiological signals to detect stress [ 13 16 ]. Almost all past approaches analyzed a combination of physiological signals, including signals collected from the electrocardiogram [ 17 ], electrodermal activity [ 18 ], and electromyography [ 19 ] sensors.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that the chosen physiological parameters are sensible from a psychophysiological and emotion psychological perspective, according with a review of Autonomic Nervous System activity in emotions [57]. The measurements were collected in a laboratory setting with the Empatica E4 and BioHarness (Zephyr, Boulder, CO, USA, a chest belt measuring a variety of cardiological parameters) selected after technology evaluation and laboratory tests [58].…”
Section: Biosensing Data-developing An Algorithm To Identify 'Momentsmentioning
confidence: 71%
“…We assess the physiological signals resulting from perceptions and emotions of pedestrians using wearable biosensors. Based on technology evaluation and laboratory tests [ 52 ], we recommend the Empatica E4 (a wristband measuring GSR and ST) and the Zephyr Bioharness (a chest strap measuring a variety of cardiological parameters like ECG, HRV, and others). Our sensor fusion method extracts emotion information (moments of stress) from the measured data using a customized signal analysis procedure [ 53 ].…”
Section: Methodsology: a Mixed-methods Approach For Analyzing Urbanmentioning
confidence: 99%